11. A CASE OF EXTRANODAL MARGINAL ZONE LYPHOMA OF MUCOSA-ASSOCIATED LYMPHOID TISSUE (MALT) TYPE AND HEPATOCELLULAR CARCINOMA. (February 2015) - Eykman, Elizabeth; Theocharous, Con
Abstract : Primary hepatic mucosa-associated lymphoid tissue (MALT) lymphoma is a rare disease. MALT lymphoma is a type of low grade extranodal B-cell lymphoma which is commonly diagnosed in the stomach where there is a well-documented association with Helicobacter pylori infection. In reported cases of primary liver MALT, it is often an incidental finding during imaging or surgery for other disease and patients usually do not have symptoms specifically related to the lymphoma. The information available from reported cases of primary liver MALT lymphoma have included associated inflammatory diseases of the liver including hepatitis B or hepatitis C (either with or without cirrhosis) or primary biliary cirrhosis. This supports the role of chronic inflammation in the pathogenesis of the condition regardless of primary site. As primary hepatic MALT lymphoma is usually asymptomatic it is likely to be an under-reported diagnosis. Only one case of concurrent hepatocellular carcinoma with hepatic MALT lymphoma on a background of hepatitis B infection is reported in the literature. We present a case of a 62 year old patient who presented with non-cirrhotic hepatocellular carcinoma on a background of cleared chronic hepatitis B infection. The patient has positive hepatitis B core antibody with negative hepatitis B surface antigen. The right hepatectomy specimen showed moderately differentiated hepatocellular carcinoma as well as an incidental diagnosis of extranodal marginal zone lymphoma of MALT type and the gallbladder specimen also showed involvement. We present this additional case of concurrent hepatocellular carcinoma and hepatic MALT lymphoma to bring to attention this extremely rare entity.